The role of Small Group Discussion (SGD) in enhancing midwifery students' learning outcomes - Dewi Ratnasari; Ari Indra Susanti (Universitas Pendidikan Indonesia, 2025)
Active learning methods such as Small Group Discussion (SGD) have been identified as an effective approach in midwifery education. This study aims to evaluate the role of SGD in enhancing midwifery students' learning outcomes, particularly in the development of cognitive aspects, critical thinking, communication, and collaboration skills. Therefore, this study uses a systematic approach to assess the existing literature on the application of SGD in midwifery education. Using the Systematic Literature Review (SLR) method and following the PRISMA guidelines, articles were selected from four main databases: Scopus, PubMed, Google Scholar, and ScienceDirect, with publications from 2020 to 2025. The analysis results show that SGD has a positive impact on concept understanding, student engagement, and the strengthening of their soft skills, including communication and teamwork abilities. SGD also fosters an interactive and reflective learning environment, making the learning process more engaging and meaningful. Additionally, SGD enhances students' ability to work in teams, which is essential in the healthcare field. Given the importance of effective teamwork in healthcare professions, developing soft skills is crucial for students. Therefore, integrating SGD into the midwifery curriculum is highly recommended to prepare students for professional challenges and the increasingly complex dynamics of the workforce. Abstrak Metode pembelajaran aktif seperti Small Group Discussion (SGD) telah diidentifikasi sebagai pendekatan yang efektif dalam pendidikan kebidanan. Penelitian ini bertujuan untuk mengevaluasi peran SGD dalam meningkatkan hasil belajar mahasiswa kebidanan, khususnya dalam pengembangan aspek kognitif, kemampuan berpikir kritis, komunikasi, dan kolaborasi. Untuk itu, penelitian ini menggunakan pendekatan yang sistematik untuk menilai literatur yang ada mengenai penerapan SGD dalam pendidikan kebidanan. Dengan menggunakan metode Systematic Literature Review (SLR) dan panduan PRISMA, artikel-artikel dipilih dari empat basis data utama: Scopus, PubMed, Google Scholar, dan ScienceDirect, dengan publikasi yang diterbitkan antara 2020 hingga 2025. Hasil analisis menunjukkan bahwa SGD memiliki pengaruh positif terhadap pemahaman konsep, keterlibatan aktif mahasiswa, dan penguatan soft skills mereka, termasuk kemampuan komunikasi dan kerja sama. SGD juga menciptakan lingkungan pembelajaran yang interaktif dan reflektif, yang membuat proses pembelajaran lebih bermakna. Selain itu, SGD memperkuat kemampuan mahasiswa dalam bekerja dalam tim, yang sangat penting di dunia kesehatan. Mengingat pentingnya kerja tim yang efektif dalam profesi kesehatan, pengembangan soft skills menjadi krusial bagi mahasiswa. Oleh karena itu, integrasi SGD dalam kurikulum pendidikan kebidanan sangat dianjurkan untuk mempersiapkan mahasiswa menghadapi tantangan profesional dan dinamika dunia kerja yang semakin kompleks. Kata Kunci: diskusi kelompok kecil; hasil belajar; mahasiswa kebidanan